Experimental and Numerical Investigation of Characteristics of Highly Heterogeneous Rock Mechanical Responses in Tight Sandy Conglomerate Reservoir Rock Under Tri-axial Compression - Chen, Bin; Ji, Jiaqi; Lin, Jingqi; Chen, Huayong; Wang, Xueliang; Guo, Xuyang; Yang, Wentao; Lin, Jiaying (Frontiers in Earth Science, 2021)
Due to the use of horizontal wells and hydraulic fracturing, commercial tight oil production from some tight sandy conglomerate reservoirs has been achieved. Since the widely distributed gravels in the sandy matrix in conglomerate reservoir rocks are harder than the matrix, the rock mechanical response in conglomerates under compression is highly heterogeneous. This increases the complexity of understanding the hydraulic fracturing behaviors in conglomerate reservoirs. Previous tri-axial compression tests provided the stress-strain relationships of conglomerate samples as a whole, and the stress and strain in the gravels and in the sandy matrix were not investigated due to the limitation of the compression test lab. This study presents tri-axial test results for a conglomerate sample cored from a reservoir that has been economically developed. Lab results are then used to calibrate the numerical model for the simulation of the tri-axial compression process. Numerical results indicate that the elastic modulus and size of gravels have significant impacts on the axial stresses and axial strains in the conglomerate. Stress concentrations are observed in gravels due to the heterogeneous mechanical properties in the conglomerate. The reorientation of the maximum horizontal principal stress is quantified to study the mechanisms of the interaction types between hydraulic fractures and gravels embedded in the tight sandy matrix.